The Relationship Between CSR Perception of Employees and It's Impact on Their Organisational Commitment with Particular Focus to Country Nepal - Basnet, Anjana (2013)
Organisational Behaviour research identifies CSR as an influential aspect to Employee Behaviour. Thus this dissertation addresses the organisational behaviour dimension to CSR thereby looking into the impact CSR perception of employees has on one employee attitude, organisational commitment from a developing nation, Nepal’s viewpoint. CSR research on developing nation lack the focus on one stakeholder group on one hand and on the other the existing literature suggest that CSR studies looking into employee attitudes has focussed around perspective employees not existing employees.